SOLVE THE SERIES OF RLC CIRCUIT VIA THE TIME-DEPENDENT VOLTAGE SINE FUNCTION USING WRONSKIAN’S OF DIFFERENTIAL EQUATION: - Hutem, Artit; Masoongnoen, Nutnicha (PSRU Journal of Science and Technology, 2021)
In this paper, we developed the mathematics and physics of the series of RLC circuits. The purpose of this study is to calculate for finding the time-dependent electric charge and the time-dependent energy static charge that because of time-dependent voltage which in sine function by using the second-order non-homogeneous linear ordinary differential equation and integration by part technique. We find that the charge corresponds to capacitance but inversely proportional to induction. The wave group of the time-dependent energy static charge depends on the ratio between resistance with double inductance and angular frequency parameter.